Review Analysis on Scalability of Carbon Removal Methods and Regulatory Framework for Carbon Management for Companies that sell materials to remove CO2 - Nayab, Tooba; Ahmed, Talal; Wijekoon, Devindi (Journal of Applied Geoscience and Engineering, 2024)
This article provides a comprehensive overview of various carbon capture and sequestration (CCS) technologies and approaches aimed at reducing atmospheric carbon dioxide (CO2) concentrations. It evaluates the effectiveness, costs, and potential scalability of different methods proposed by companies and research organizations worldwide, including innovative technologies such as CARBiNX by Clean O2, carbon capture by forests and trees, Direct Air Capture (DAC) systems developed by Heirloom Carbon Technologies, and geological storage solutions like Carbfix in Iceland. The article also examines the costs associated with these technologies and their capacity to remove significant amounts of CO2 from the atmosphere. Furthermore, it explores future pathways and frameworks for achieving gigaton-scale carbon dioxide removal, emphasizing the importance of interdisciplinary collaboration and technological innovation in addressing the urgent challenge of climate change. Through a comprehensive analysis of current research and industry practices, this review aims to provide insights into the scalability of carbon removal methods and the regulatory landscape governing carbon management, focusing on companies that sell materials to remove CO2. It discusses the challenges and opportunities associated with scaling up carbon removal technologies and explore regulatory frameworks shaping the deployment of these technologies, offering valuable insights into the future of carbon removal and regulatory compliance for companies in the carbon removal sector.